BAHASA INGGRIS KOLOKIAL PADA CHICKLIT MINI SHOPAHOLIC KARYA SOPHIE KINSELLA - , Tri Utari Suhartinah, Prof. Dr. I Dewa Putu Wijana, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Novel is one of social documents that reflects a societyâs condition in a period of time including chicklit. Chicklit is a new genre of popular novels which describes the urban everyday life in modern time. For describing the urban everyday life, its linguistic features differ from other genre novels and even other popular novels. Its linguistic features refer to the use of colloquial language. In this research, the writer attempts to identify its linguistic features and functions which are seen from the main form i.e its lexical and grammatical features. The process of analyzing its lexical and grammatical forms as well as its functions is done by using qualitative descriptive method to an English chicklit pioneer chicklit entitled Mini Shopaholic written by Sophie Kinsella. The data is collected by analyzing the linguistic content then followed by recording it. The technique of analyzing data is done based on Guba and Lincoln theory. It is then followed by studying and comparing the data to know the lexical dan grammatical features and functions found in the research. The data are then examined by paraphrasing them when interpreting dan describing the result. The result of theresearch shows that the lexical features found cover (1) deixis covering pronoun deixis, spatial deixis dan temporal deixis